2017
DOI: 10.2298/abs160914129s
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effects of the ethanolic extract of Allium saralicum R.M. Fritsch on CCl4-induced nephrotoxicity in mice: A stereological examination

Abstract: The present study was carried out to investigate the nephroprotective effect of the ethanolic extract of Allium saralicum R.M. Fritsch (ASRMF) in mice. Thirty-five male mice were divided into five groups (n=7). Group 1 (positive control) received 1 mL/kg olive oil intraperitoneally (i.p.) and 0.5 mL distilled water orally; Group 2 (negative control) received CCl 4 (50% in olive oil, 1 mg/kg; i.p.); Groups 3, 4 and 5 received CCl 4 and 200, 800 and 1600 µg/kg of ASRMF extract, respectively. The renal volume and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 88 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…Sherkatolabbasieh et al . reported that the major component of A. saralicum ethanolic extract was linolenic acid methyl ester . Also, Zangeneh et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sherkatolabbasieh et al . reported that the major component of A. saralicum ethanolic extract was linolenic acid methyl ester . Also, Zangeneh et al .…”
Section: Introductionmentioning
confidence: 99%
“…It is distributed in Iran, Turkey and Iraq . A. saralicum has been consumed for its anti‐hyperlipidemic, anti‐inflammatory, antioxidant, hepatoprotective and nephroprotective activities . It seems that A. saralicum contains many compounds that act together to inhibit microbial disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Iran has experimental plants that are widely distributed throughout the country, particularly in Kermanshah province, west of Iran (geographical coordinates: 34.3277°N and 47.0778°E) . They have been the foundation for inhibition and treatment of experimental diseases . One of the most important herbal medicines that is widely used is Gundelia tournefortii L..…”
Section: Introductionmentioning
confidence: 99%
“…Iran has experimental plants that are widely distributed throughout the country, particularly in Kermanshah province, west of Iran (geographical coordinates: 34.3277°N and 47.0778°E) . They have been the foundation for inhibition and treatment of experimental diseases . One of the most important herbal medicines that is widely used is Ziziphora clinopodioides Lam .…”
Section: Introductionmentioning
confidence: 99%